Literatura — film — teatr. Praktyki intermedialne w spektaklach biograficznych. Studium przypadku - Popczyk-Szczęsna, Beata (Zagadnienia Rodzajów Literackich, 2020)
The starting point of these considerations in the form of a case study are two issues: intermediality as a distinguishing mark of contemporary hybrid art forms and numerous references to famous films in the latest Polish theatre. The article concerns the performance Between the mouth and the edge of the cup (directed by Remigiusz Brzyk, Zagłębie Theatre in Sosnowiec, 17.05.2019). This performance, inspired by the biography of Maria Rodziewiczówna, is an example of the corelation of various media and an autothematic show whose theme is the writer’s biography, popular novel, film and their reception.